ANALISIS RASIO ALTMAN Z-SCORE TERHADAP PREDIKSI FINANCIAL DISTRESS PERUSAHAAN REAL ESTATE YANG LISTING DI BURSA EFEK INDONESIA - Dian Wulan Sari (Jurnal AkunStie (JAS), 2019)
Financial statements are the heart of the company in order to grow and develop in accordance with the objectives of the company's organization. For this reason, special tools are needed that can predict financial health in order to avoid financial distress or financial difficulties, one of which uses the Altman Z-Score ratio which consists of 5 variables namely Working Capital to Total Assets (X1); Retained Earning to Total Assets (X2); Earnings Before Interest and Taxes to Total Assets (X3); Market Value Equity to Book Value of Total Debt (X4); and Sales to Total Asstes (X5). This research is a quantitative study with data analysis techniques using Multiple Regression Analysis. The study population was property and real estate companies listing on the IDX with 90 samples.The results of this study indicate that the MKTA variable (X1); LATA (X2); EBITA (X3); NPTU (X4); and PETA (X5) have a significant and partially significant effect on the Financial Distress variable on Real Estate Companies listing on the IDX with a confidence level of 95% (sig. 0.05). This research is expected to be used as a reference or reference to other similar research so that the techniques and results obtained are of higher quality.